9.7k views
3 votes
Simplify
x² - 9 / х^2 - 3x

Simplify x² - 9 / х^2 - 3x-example-1

2 Answers

3 votes
Here is the answer!:)
Simplify x² - 9 / х^2 - 3x-example-1
User Semaphor
by
5.0k points
2 votes

Answer:


(x+3)/(x)

Explanation:

Factorise numerator and denominator

x² - 9 ← is a difference of squares and factors in general as

a² - b² = (a - b)(a + b) , then

x² - 9

= x² - 3² = (x - 3)(x + 3)

x² - 3x ← factor out x from each term

= x(x - 3)

Then


(x^2-9)/(x^2-3x)

=
((x-3)(x+3))/(x(x-3)) ← cancel common factor (x - 3) on numerator/denominator

=
(x+3)/(x)

User Walkerlala
by
5.7k points